2007
DOI: 10.1088/0953-4075/40/21/004
|View full text |Cite
|
Sign up to set email alerts
|

Nonperturbative resonant strong field ionization of atomic hydrogen

Abstract: We investigate resonant strong field ionization of atomic hydrogen with respect to the 1s-2p-transition. By "strong" we understand that Rabi-periods are executed on a femtosecond time scale. Ionization and AC Stark shifts modify the bound state dynamics severely, leading to nonperturbative signatures in the photoelectron spectra. We introduce an analytical model, capable of predicting qualitative features in the photoelectron spectra such as the positions of the Autler-Townes peaks for modest field strengths. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 38 publications
4
22
0
2
Order By: Relevance
“…The differential equations (6) have to be supplemented with initial conditions. In what follows, we shall assume that the laser field is switched on instantaneously at t = 0 when atoms A and B are in their ground states.…”
Section: General Considerationmentioning
confidence: 99%
See 1 more Smart Citation
“…The differential equations (6) have to be supplemented with initial conditions. In what follows, we shall assume that the laser field is switched on instantaneously at t = 0 when atoms A and B are in their ground states.…”
Section: General Considerationmentioning
confidence: 99%
“…Electronic correlations can be particularly clearly manifested in photoionization of atoms and molecules. Prominent examples include, but are not limited to, single-photon double ionization [2], laser-induced autoionization [3,4], and nonsequential double ionization in strong laser fields [5,6]. When an atom is not isolated in space but is a neighbor to another (distant) atom, the electronic structures of these two centers can be coupled by a long-range electromagnetic interaction leading to various interesting phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the well-known Autler-Townes effect 27 emerges in the spectral domain as a manifestation of Rabioscillations, and thus any signature of dynamic interference should be disentengled from the above-mentioned effect. In this resonant dynamics, it was found that, when the electric field is strong enough to induce many Rabi-cycles, additional sub-peaks were observed in the angle-integrated spectrum accompanied with the Autler-Townes doublet 25,[28][29][30] . Here, most theoretical works have focused on discussing only the Autler-Townes doublet (see e.g.…”
Section: Introductionmentioning
confidence: 95%
“…We first consider the one-colour scheme which consists of the fundamental harmonic that is resonant with the 1s − 2p transition. This resonant two-photon ionization process has been discussed extensively and mostly in connection with the photoelectron spectrum 25,[28][29][30][31] . At this resonant frequency of a strong electric field, Rabi flopping is expected to emerge in the occupation probabilities oscillating between the states 1s and 2p in time domain.…”
Section: One-colour Schemementioning
confidence: 99%
“…Single-electron dynamics has served to debut many established methods [1][2][3][4][5][6][7][8][9][10][11][12][13]. We extend a highly-accurate method of computational chemistry [14][15][16][17] towards a robust description of many-electron systems, beyond the single-electron approximation.…”
Section: +mentioning
confidence: 99%